Retrospective analysis of non-invasive prenatal testing: a population study involving 19,835 participants in the Shaoyang area - Zhou, Muping; Zhang, Hua; Wen, Jun; Liu, Na; Wu, Zhongchun; Lin, Ting; Tang, Mengyun; Huang, Yan; Xiao, Ying; Xie, Hui; Ouyang, Xia; Xiao, Xiang; et al. (Frontiers in Genetics, 2026)
BackgroundThis cohort study aimed to evaluate the clinical efficacy of Non-invasive prenatal testing (NIPT) in detecting fetal chromosomal abnormalities within a pregnant population in the Shaoyang area, and to further investigate the potential correlation between parental ages and the risk of such abnormalities.MethodsA cohort study was conducted involving 19,835 pregnant women recruited for NIPT between October 2019 and April 2024. The performance of NIPT was assessed based on its positive predictive value (PPV), sensitivity, and specificity. The relationship between parental age and chromosomal abnormalities was analyzed.ResultsWe identified 88 positive cases, among which Trisomy 13, 18, and 21 accounted for 64 cases. The total PPV was 75.29%. Additionally, we detected 28 cases of sex chromosomal aneuploidies, with an overall PPV of 24.56%. The detection rate of autosomal abnormalities was higher in parents aged 35 years or older (5.49‰) compared to that in the younger parental age group (2.62‰). Unexpectedly, the sex chromosomal abnormalities exhibited an opposite trend, with the younger group demonstrating a higher detection rate of 1.31‰ than the advanced parental age group (0.61‰). All 7 cases of 47,XXY were concentrated among parents under 35 years of age. These results indicate that advanced parental ages are associated with an increased risk of autosome abnormalities; conversely, younger parental ages appear to correlate with a heightened risk of sex chromosome abnormalities.ConclusionParental ages may thus influence the occurrence of chromosome abnormalities. Our findings provide novel insights for prenatal genetic counseling.